2023
DOI: 10.11609/jott.8336.15.6.23452-23454
|View full text |Cite
|
Sign up to set email alerts
|

War prompts distress symptoms in Israeli Blind Snake

Abstract: During a series of explosions in a recent eruption of violence between Israel and Gaza, the metabolic rate of a Syrian Blind Snake Xerotyphlops syriacus peaked acutely, and its breathing pattern changed. This is the first record of a wild animal’s real-time physiological response to the noise of an incoming rocket attack and highlights the gap in our understanding of how anthropogenic noise – and military activity in general – affects individual wildlife.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…However, the lizard Aspidoscelis neotesselatus has shown stress responses in reaction to military jet flyovers, including higher blood ketone and corticosterone levels, and more time spent foraging afterward as compensation for lost energy (Kepas et al, 2023). Dubiner et al (2023) recently reported evidence of a sharp increase in the respiration of a single individual blind snake Xerotyphlops syriacus during a 2021 rocket attack on Tel Aviv. Sadly, while conducting a long-term experiment on the physiology of geckos, the eruption of the war between Israel and Hamas allowed us to empirically test and quantify the real-time effects of repeated bombings on reptile metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lizard Aspidoscelis neotesselatus has shown stress responses in reaction to military jet flyovers, including higher blood ketone and corticosterone levels, and more time spent foraging afterward as compensation for lost energy (Kepas et al, 2023). Dubiner et al (2023) recently reported evidence of a sharp increase in the respiration of a single individual blind snake Xerotyphlops syriacus during a 2021 rocket attack on Tel Aviv. Sadly, while conducting a long-term experiment on the physiology of geckos, the eruption of the war between Israel and Hamas allowed us to empirically test and quantify the real-time effects of repeated bombings on reptile metabolism.…”
mentioning
confidence: 99%
“…We assume the increased metabolic costs indicate an acute stress response, initiated by the loud noise or vibrations from the explosions (Dubiner et al, 2023) and continuing, to a lesser degree, several hours after. Despite ranging from the Day 4 to Day 32 of the war, the geckos' response did not attenuate.…”
mentioning
confidence: 99%